HOW DOES POST-NEEDLING SORENESS DIFFER BETWEEN THE IN-OUT AND ROLLING DRY NEEDLING TECHNIQUES ? - Bayu Prastowo; Nurul Intan Fadhilah; Dia Rafidya Tamimi; Syi’ar Aprilla Tanazza (Universitas Muhammadiyah Metro, 2026)
Introduction: Post-Needling Soreness is the most frequently reported transient adverse event following dry needling and may negatively affect patient comfort and treatment adherence. This study aimed to compare the severity of Post-Needling Soreness between the In-Out and Rolling dry needling techniques in individuals with upper trapezius Myofascial Trigger Point Syndrome (MTrPS). Method: A quasi-experimental study was conducted involving 92 participants with upper trapezius MTrPS. Post-Needling Soreness was assessed using the Visual Analog Scale (VAS) at 0.5, 24, 48, and 72 hours after the intervention. Differences between groups at each time point were analyzed using the Mann-Whitney U test, while changes over time and interaction effects were examined using mixed ANOVA. Result: The Rolling technique produced significantly greater Post-Needling Soreness than the In-Out technique at 0.5 hours post-intervention (p=0.026). However, no significant between-group differences were observed at 24, 48, or 72 hours (p>0.05). Mixed ANOVA demonstrated significant main effects of dry needling technique (p=0.029) and time (p<0.001). That interaction between technique and time was not statistically significant (p=0.456). Conclusion: Both groups exhibited a progressive reduction in Post-Needling Soreness throughout the 72 hour follow-up period. The In-Out technique resulted in lower acute Post-Needling Soreness than the Rolling technique, although both techniques demonstrated a similar recovery profile over 72 hours. These findings suggest that the In-Out technique may be preferable when minimizing immediate post-treatment discomfort is a clinical priority.